2021
DOI: 10.1002/fsn3.2461
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the possibility of fermentation of red grape juice and rice flour by Lactobacillusplantarum and Lactobacilluscasei

Abstract: Microorganisms and their fermentative activities have had a distinctive role in human being as old as civilization (Erten et al., 2014;Mith et al., 2014). A broad variety of foods and beverages have been produced by fermentative activities of microorganisms, which finally led to desirable biochemical changes in different foods (Blandino et al., 2003;Ferreira et al., 2000). Decreasing the volume of material to be transported, increasing the nutritive value, degrading undesirable component, reducing the cooking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The production of various organic acids may be the main reason for the decrease in pH [ 26 ]. The above results are supported by the study of Mirmohammadi et al [ 27 ]. They concluded that the pH values of different substrates decrease rapidly within 12 h after fermentation by LAB.…”
Section: Resultssupporting
confidence: 83%
“…The production of various organic acids may be the main reason for the decrease in pH [ 26 ]. The above results are supported by the study of Mirmohammadi et al [ 27 ]. They concluded that the pH values of different substrates decrease rapidly within 12 h after fermentation by LAB.…”
Section: Resultssupporting
confidence: 83%
“…This can be explained by the gradual degradation of citric acid by lactic acid bacteria. As shown by Mirmohammadi et al [ 57 ], L. plantarum are able to metabolize citric acid as a carbon source during fermentation. C4 aromatic compounds may be the end product of these transformations.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Moreover, co-fermentation with two Lactobacillus strains has been demonstrated to be more effective than that of a single strain. 25,26 Cerasus humilis, locally known as Ouli, is a unique functional fruit and medicinal resource in China. The fruit of C. humilis has a unique sweet and sour flavor and is rich in vitamins, amino acids, flavonoids, and polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Moreover, co-fermentation with two Lactobacillus strains has been demonstrated to be more effective than that of a single strain. 25,26…”
Section: Introductionmentioning
confidence: 99%